2019
DOI: 10.1002/jssc.201900910
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant trehalose lipid‐enhanced ultrasound‐assisted micellar extraction and determination of the main antioxidant compounds from functional plant tea

Abstract: Hydrosoluble trehalose lipid (a biosurfactant) was employed for the first time as a green extraction solution to extract the main antioxidant compounds (geniposidic acid, chlorogenic acid, caffeic acid, and rutin) from functional plant tea (Eucommia ulmoides leaves). Single‐factor tests and response surface methodology were employed to optimize the extraction conditions for ultrasound‐assisted micellar extraction combined with ultra‐high‐performance liquid chromatography in succession. A Box‐Behnken design (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The identification of Eucommia ulmoides and their extracts have been a hot spot in the research and utilization of Eucommia ulmoides. Our study showed that the water extract of EUL contained lignans, iridoids, phenylpropanoids, flavonoids, and so on, which is consistent with that extracted by organic solvent [52,53]. However, the water extract has the advantages of low cost, simple operation, and less pollution.…”
Section: Discussionsupporting
confidence: 79%
“…The identification of Eucommia ulmoides and their extracts have been a hot spot in the research and utilization of Eucommia ulmoides. Our study showed that the water extract of EUL contained lignans, iridoids, phenylpropanoids, flavonoids, and so on, which is consistent with that extracted by organic solvent [52,53]. However, the water extract has the advantages of low cost, simple operation, and less pollution.…”
Section: Discussionsupporting
confidence: 79%
“…The authors of discussed works have chosen among the classic compounds, i.e., cationic CTAB, anionic SDS, or the particularly popular non-ionic compounds such as Triton X-100, Triton X-114, or Genapol X-080. The use of ionic liquids (the IL-type surfactants), i.e., decylguanidinium chloride [ 66 ], C 16 C 4 Im-Br [ 67 ], C 12 mim-Cl [ 68 ], and biosurfactants, i.e., trehalose lipid [ 69 ], hyodeoxycholic acid sodium salt [ 70 ], or synthetic sugar surfactant APG0810 [ 71 ] are still the innovations in this field.…”
Section: Nano-micellar Extraction Of Polyphenolsmentioning
confidence: 99%
“…The authors related this effect to the position of the hydroxyl groups in the sodium salt of hyo -deoxycholic acid. Some substitutions promote hydrogen bond formation and electrostatic interactions with analytes that further increase the mass transfer of the target analytes from sample powder to the aqueous phase [ 69 ]. Therefore, the hydroxyl group at the C6 position is quite unique when compared to the bile salts of human origin.…”
Section: Nano-micellar Extraction Of Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfactants in micellar mobile phases modify stationary phases by masking silanol groups that in turn resulted in improving the peak shape. Surfactants had been applied in determination of drug mixtures when mixed with a small proportion of organic solvent [3][4][5][6][7], applied as green extraction technique [8,9], or sometimes applied as stationary phase replacement (pseudo-phase) [10,11].…”
Section: Introductionmentioning
confidence: 99%